Return to Sport After Surgical Treatment for Anterior Shoulder Instability: A Systematic Review. Issue 6 (May 2019) - Abdul-Rassoul, Hussein; Galvin, Joseph W.; Curry, Emily J.; Simon, Jason; Li, Xinning
Background: For athletes, a return to preinjury activity levels with minimal time away is a metric indicative of successful recovery. The knowledge of this metric would be helpful for the sports medicine specialist to advise patients on appropriate expectations after surgery. Purpose: To evaluate the rate and amount of time needed for athletes to return to sport (RTS) after different surgical treatments for anterior shoulder instability. Study Design: Systematic review and meta-analysis. Methods: The MEDLINE, EMBASE, and Cochrane databases were searched for articles relevant to athletes' RTS after surgical anterior shoulder stabilization with variants of the Latarjet and Bankart procedures. Article selection was based on relevant inclusion and exclusion criteria. After the articles were reviewed, the data pertinent to rates of and time to RTS were extracted, compiled, and analyzed. Results: Sixteen articles met the inclusion criteria. Based on these articles, the rate of RTS was 97.5% after arthroscopic Bankart, 86.1% after open Bankart, 83.6% after open Latarjet, 94.0% after arthroscopic Latarjet, and 95.5% after arthroscopic Bankart with remplissage. Among the athletes who did RTS, arthroscopic Bankart had the highest rate of return to preinjury levels (91.5%), while arthroscopic Latarjet had the lowest rate (69.0%). The time to RTS was 5.9 months after arthroscopic Bankart, 8.2 months after open Bankart, 5.07 months after open Latarjet, 5.86 months after arthroscopic Latarjet, and 7 months after arthroscopic Bankart with remplissage. Conclusion: Of the pooled data, patients who underwent arthroscopic Bankart showed the highest rate of RTS, while patients who underwent open Latarjet showed the shortest time to RTS. Return to preinjury level was highest in the arthroscopic Bankart group and lowest in the arthroscopic Latarjet group. Physicians can utilize these data to set expectations for their patient-athletes regarding RTS after anterior shoulder stabilization procedures. Clinical Relevance: When treating an athlete, many factors must be taken into account to weigh treatment options. Two important factors to consider with the patient-athlete are the rate of return to the previous activity level and the timeline for this to occur. This study provides a guide for physicians and a time frame for athletes with respect to the mean percentage and time for return to sport after different surgical procedures for anterior shoulder instability.